Respiratory Distress in Nigerian Neonates - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Facilities for neonatal respiratory support are not available in many centres in developing countries, and hence, there is a need to recognize and prevent the predisposing factors to respiratory distress (RD) among high-risk neonates. This study sets out to determine the prevalence, severity, etiological, and risk factors as well as outcome of babies with RD at the Wesley Guild Hospital (WGH), Ilesa, Nigeria.Materials and Methods:Neonates admitted to the Special Care Baby Unit of the hospital were consecutively recruited into a prospective observational study over a 10-month period. History, examination, and investigation findings were compared among babies with and without RD at presentation.Results:The ages at presentation of the 428 babies ranged from 20 minutes to 25 days [Median (IQR) of 4.0 (1.0–35.0) hours]; male:female 1.4:1 and 32.5% were preterms. Two hundred and fifty (58.4%) had RD, and the major identifiable causes were asphyxia (53.6%), sepsis (24.0%), respiratory distress syndrome (16.4%), and transient tachypnoea of the newborn (10.0%). Lack of antenatal care, low birth weight/preterm delivery, primiparity, and delivery in private hospitals were risk factors to having RD. The presence of RD was associated with hypoxemia, increased mortality (17.2% vs. 4.5%), and length of hospitalization among the babies (P< 0.001).Conclusion:RD is a common presentation among ill neonates and is associated with prolonged hospitalization and death. Many of its predisposing factors are, however, preventable. Making essential obstetric and neonatal care available and affordable will reduce the burden associated with neonatal RD in developing countries.